Conference. Gulf Arab countries and the Armenian communities: current trends and issues (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
On July 4, 2022, the Institute of Oriental Studies of the NAS RA organized an international conference. Leading researchers from the Gulf countries (UAE, Kuwait, Qatar), Institute of Oriental Studies NAS RA, Yerevan State University and V. Brusov State University made presentations during the conference.
Keywords: Conference